Assimilation and translocation of nitrogen and carbon in Curcuma alismatifolia Gagnep - Khuankaew T. (2014)
Curcuma or Siam tulip (Curcuma alismatifolia Gagnep.) is an ornamental flowering plant with two underground storage organs, rhizomes and storage roots. Characteristics of N and C assimilation and transport in curcuma were investigated. The plants were treated with 15NH4+ + 15NO3- and 13CO2 at 10, 13 or 21 weeks after planting. Plants were sampled at several stages up to 32 weeks. The C stored in old storage roots was used rapidly during the first 10 weeks; after which N stored in old rhizomes and old storage roots were used. The daily gain in C depending on photosynthesis was remarkably high between 10 and 21 weeks. However, the daily gain in N was relatively constant throughout the growth period. The 15N absorbed at 10 weeks was initially accumulated in leaves and roots, but some was transported to flowering organs at 13 weeks. At harvest, 41% of 15N was recovered in new rhizomes and 17% in new storage roots. After 13CO2 exposure at 10 and 13 weeks, the distribution of 13C among organs was relatively constant in subsequent stages. When given 13CO2 at 21 weeks, a large amount of labelled C was recovered in new storage roots and new rhizomes at harvest. Both new rhizomes and new storage roots stored N and C, however, rhizomes played a more important role in supplying N, while storage roots provided C. © 2009 German Botanical Society and The Royal Botanical Society of the Netherlands.